1990
DOI: 10.1002/bip.360300702
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric study on hydration of B‐, A‐, and Z‐DNA

Abstract: Dielectric relaxation peak due to bound water was found around 100 MHz in poly(dG-dC).poly(dG-dC) and calf thymus DNA in water-ethanol mixtures with NaCl buffer. Relaxation time and strength show a transition for poly(dG-dC).poly(dG-dC) at an ethanol composition Cw = 0.45 (w/w) where the structural transition from B- to Z-DNA takes place. It has been suggested that the transition is caused by removal of the bound water molecules preferentially from the phosphate groups. If the bound water molecules are removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 43 publications
3
50
0
1
Order By: Relevance
“…Time windows employed were 5 mad 20 ns for the shorter cell and 50, 100, 200, 500 ns, 1, 2, 5, and 10 Ixs for the longer cell. By using these cells, even very small relaxation with a relaxation strength of the magnitude of 0.1 may be measured in the frequency region of concern (Umehara et al, 1990). For the overlapping region of frequency between 100 MHz and 1 GHz, data obtained by the two cells were in agreement.…”
Section: Tdr Methodsmentioning
confidence: 74%
“…Time windows employed were 5 mad 20 ns for the shorter cell and 50, 100, 200, 500 ns, 1, 2, 5, and 10 Ixs for the longer cell. By using these cells, even very small relaxation with a relaxation strength of the magnitude of 0.1 may be measured in the frequency region of concern (Umehara et al, 1990). For the overlapping region of frequency between 100 MHz and 1 GHz, data obtained by the two cells were in agreement.…”
Section: Tdr Methodsmentioning
confidence: 74%
“…X-ray crystallography, NMR, dielectric relaxation, and molecular dynamics simulation studies have shown that a significant amount of water molecules are bound to DNA (for reviews, see refs. [2][3][4][5][6]. For example, measurements of dielectric relaxation caused by water molecules bound to DNA in mixed water-ethanol solutions have found that 18-19 water molecules per nucleotide are present in B-DNA, but only 13-14 water molecules are bound in A-DNA (5).…”
mentioning
confidence: 99%
“…[2][3][4][5][6]. For example, measurements of dielectric relaxation caused by water molecules bound to DNA in mixed water-ethanol solutions have found that 18-19 water molecules per nucleotide are present in B-DNA, but only 13-14 water molecules are bound in A-DNA (5). The study also suggested that a structural transition of poly(dG-dC)⅐poly(dGdC) DNA from its B to Z form takes place on the removal of the bound water molecules, preferentially from the phosphate groups.…”
mentioning
confidence: 99%
“…Studies of water vapour adsorption of DNA films by IR spectroscopy have shown that the hydrogen bonded water peak maxima shifted from 3473 to 3583 cm -1 as moisture content increases. This was attributed to the formation of a thin liquid water film on the surface of DNA [6].The interaction between DNA and water were described by quantum mechanical methods [2] and by molecular dynamics [7]. Water network around simulated duplexes was more conformation specific rather than sequence specific [7].…”
mentioning
confidence: 99%
“…Studies of water vapour adsorption of DNA films by IR spectroscopy have shown that the hydrogen bonded water peak maxima shifted from 3473 to 3583 cm -1 as moisture content increases. This was attributed to the formation of a thin liquid water film on the surface of DNA [6].…”
mentioning
confidence: 99%